Economic Analysis of Low Volume Interventions Using Real-World Data: Costs of HIV Self-Testing Distribution and HIV Testing Services in West Africa From the ATLAS Project - Traore, Métogara Mohamed; Badiane, Kéba; Vautier, Anthony; Simo Fotso, Arlette; Kanku Kabemba, Odé; Rouveau, Nicolas; Maheu-Giroux, Mathieu; Boily, Marie-Claude; Larmarange, Joseph; Terris-Prestholt, Fern; d'Elbée, Marc (Frontiers in Health Services, 2022)
Achieving the first 95 of the UNAIDS targets requires the implementation of innovative approaches to knowing one's HIV status. Among these innovations is the provision of HIV self-testing (HIVST) kits in west Africa by the international partner organization Solthis (IPO). In order to provide guidance for the optimal use of financial resources, this study aims to estimate the program and site level costs of dispensing HIVST as well as HIV testing services (HTS) - excluding HIVST - in health facilities in Côte d'Ivoire, Mali and Senegal as part of the ATLAS project. We estimated from the provider’s perspective, HIVST and HTS incremental costs using top-down and bottom-up costing approaches and conducted a time and motion study. We identified costs at the program level for HIVST (including IPO central costs) and at the site level for HIVST and HTS. The economic costs of distributing HIVST kits were assessed in 37 health facilities between July 2019 and March 2021 (21 months). Sensitivity analyses were also performed on unit costs to examine the robustness of our estimates related to key assumptions. In total, 16,001 HIVST kits were dispensed for 32,194 HTS sessions carried out. Program level HIVST average costs ranged $12-$286, whereas site level costs ranged $4-$26 across distribution channels and countries. Site level HTS costs ranged $7-$8 per testing session, and ranged $72-$705 per HIV diagnosis. Across countries and channels, HIVST costs were driven by personnel (27%-68%) and HIVST kits (32%-73%) costs. The drivers of HTS costs were personnel costs ranging between 65% and 71% of total costs across distribution channels and countries, followed by supplies costs between 21% and 30%. While program level HIVST average costs were high, site level HIVST average costs remained comparable to HTS costs in all countries. Health facility-based distribution channels operating at low volume exhibit high proportion of central costs which should be considered carefully for financial planning when run alongside high volumes mobile outreach distribution channels. HIVST can diversify the HIV testing offer at health facilities, thus improving access to screening for target populations not reached by HTS services.